CHANGES IN ORGANS AND TISSUES OF THE ORAL CAVITY IN NEW CORONAVIRUS INFECTION (COVID-19) - Giyazova Malika Muxamadovna (World Scientific Research Journal, 2025)
Annotation. This scientific article is devoted to the study of changes in the organs and tissues of the oral cavity caused by the new coronavirus (SARS-CoV-2) infection during the COVID-19 pandemic. The effect of coronavirus on the oral cavity is comprehensive and complex, and various symptoms and pathological conditions can occur in this area. In this article, we will look at how COVID-19 infection causes inflammation, hardening, ulcers in the oral cavity and related tissues, as well as changes in oral hygiene and dental conditions. Studies show that the coronavirus affects not only the respiratory system, but also the oral cavity and its supporting structures, which can lead to medium- and long-term dental health problems.The article also presents pathological conditions in the oral cavity (for example, stomatitis, gingivitis, periodontitis) and their relationship with COVID-19, as well as recommendations aimed at improving the methods of clinical diagnosis and treatment of these changes. Expansion of information on the impact of COVID-19 on the oral cavity will allow dental workers and general practitioners to develop effective diagnostic and treatment strategies.